Everyday Flux of Smallholder Beef Farming: System Overview of the Beef Farming Situation Under a Government Grant - Setianto, Novie Andri; Cameron, D; Gaughan, J B (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. Smallholders dominate the beef farming in Indonesia. As a complex system, developing the smallholders need to be approached using a system thinking study. This study aimed to explore everyday activities of the smallholder beef farming which lead to an identification of any unfavorable conditions of the current situation. This is an initial step of a systems thinking approach. Descriptive study involving stakeholders of smallholder farmers group have been undertaken in KabupatenBanyumas and Banjarnegara. Descriptive analysis was performed, and a qualitative model was developed to mimic the current beef farming in both locations. Result showed that there is a growing tendency of shifting from breeding to fattening, buying and selling conditions were disadvantageous for smallholders, and the availability of grant encourage side-tracking behavior which confirmed in the model. Key words: smallholders, beef farming, side-tracking, qualitative model, systems thinking Abstrak. Peternakan sapi di Indonesia didominasi oleh peternak kecil dalam sebuahsistem yang kompleks. Dibutuhkan pendekatan sistem untuk mempelajari sistemtersebut. Penelitianini bertujuan mengkaji aktivitas sehari-hari yang terjadi dalam sebuah sistem usaha peternakan sapi potong skala kecil untuk mengidentifikasi aktivitas yang berpotensi menjadi sumber permasalahan. Identifikasi permasalahan merupakan awal penting dari sebuah analisis sistem. Studi ini menggunakan pendekatan deskriptif dengan melibatkan pemangku kepentingan yang terkait dengan sistem usaha peternakan sapi potong di Kabupaten Banyumas dan Banjarnegara. Data dianalisis menggunakan pendekatan deskriptif dan pemodelan kualitatif. Penelitian menunjukkan adanya kecenderungan peternak untuk bergeser dari pembibitan kearah penggemukan, praktik jual beli yang tidak berpihak pada peternak, dan kecenderungan bertambahnya side-tracker dengan meningkatnya hibah. Kata kunci: peternak kecil, peternakan sapi potong, side-tracking, pemodelan kualitatif, systems thinking